(untitled) (Journal of Pathology of Nepal, 2013)
The acute myeloid leukemias are genetically a diverse group of neoplasm with varied clinical behavior and response to treatment. Advances in immunophenotyping, cytogenetics and molecular genetics have resulted in better understanding of their genesis. Risk stratification of different variants is now emerging. Therapy strategies are now increasingly being developed considering the inherent biological behavior of the different subtypes. It is anticipated that in the future, deeper secrets of these once fatal diseases will be unraveled by advances in newer genomic techniques. It is hoped that future use of gene specific tailored therapy and strategies will result in longer survival in cases showing poorer prognosis at present. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9001 Journal of Pathology of Nepal (2013) Vol. 3, 497-501